1999
DOI: 10.1038/14814
|View full text |Cite
|
Sign up to set email alerts
|

Neural strength of visual attention gauged by motion adaptation

Abstract: Single-cell and neuroimaging studies reveal that attention focused on a visual object markedly amplifies neural activity produced by features of the attended object. In a psychophysical study, we found that visual attention could modulate the strength of weak motion signals to the point that the perceived direction of motion, putatively registered early in visual processing, was powerfully altered. This strong influence of attention on early motion processing, beside complementing neurophysiological evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 28 publications
6
63
0
1
Order By: Relevance
“…The discrepancy between the activation patterns observed with different attention tasks further emphasize the special case of selective attention tasks that focus directly on motion perception and is in agreement with the previous literature (Alais and Blake 1999;Culham et al 2000;Lankheet and Verstraten 1995;Mukai and Watanabe 2001;Shulman 1993;Sohn et al 2001).…”
Section: Selective Attention and Mae Processingsupporting
confidence: 91%
See 1 more Smart Citation
“…The discrepancy between the activation patterns observed with different attention tasks further emphasize the special case of selective attention tasks that focus directly on motion perception and is in agreement with the previous literature (Alais and Blake 1999;Culham et al 2000;Lankheet and Verstraten 1995;Mukai and Watanabe 2001;Shulman 1993;Sohn et al 2001).…”
Section: Selective Attention and Mae Processingsupporting
confidence: 91%
“…It is worth noting in this context that even weak motion signals can be modulated by selective attention (Alais and Blake 1999;Seidemann and Newsome 1999;Treue and Martinez Trujillo 1999) or contextual influences (Kozak and Castelo-Branco 2009). Huk et al in 2001 observed no net MAE-related increase of hMT ϩ activity in a task directed to near threshold stimulus motion and interpreted this result as an indication that the observed BOLD response characteristics were explained by shifts in attention and/or nonspecific effects of arousal.…”
Section: Introductionmentioning
confidence: 92%
“…If this were true, attention would simply increase the contribution of the attended stimulus to the net SMAE (Alais and Blake, 1999) as known from the biased competition framework (Desimone and Duncan, 1995). While this again cannot explain the repulsion effect, it could be a possible explanation for the observed attraction.…”
Section: Resultsmentioning
confidence: 97%
“…Although this link was not made explicit by Fang et al (2009), it has important implications for the complex mechanisms serving attention and adaptation. However, in studies of tilt (Spivey and Spirn, 2000) and motion (Alais and Blake, 1999) aftereffects, attention during adaptation produced stronger aftereffects.…”
mentioning
confidence: 87%